3-MA Enhanced Chemosensitivity in Cisplatin Resistant Hypopharyngeal Squamous Carcinoma Cells via Inhibiting Beclin -1 Mediated Autophagy - Zhang, Jia; Mao, Wei; Liu, Yuying; Ding, Jian; Wang, Jie; Yu, Ziwei; Huang, Ruofei; Yang, Sen; Sun, Ying; Dong, Pin (Current Pharmaceutical Design, 2021)
Background: Hypopharyngeal carcinoma is characterized by a high degree of malignancy. The most common pathological type is squamous cell carcinoma (HSCC). Cisplatin (cis-diamminedichloroplatinum, CDDP) is one of the most widely used chemotherapeutic drugs nowadays and cisplatin resistance is a major problem in current treatment strategies. Clinical researchers have reported that high autophagy levels often caused insensitivity to chemotherapy, a common phenomenon that greatly reduces the therapeutic effect in cisplatin- resistant tumor cell lines. 3-methyladenine (3-MA), an inhibitor of PI3K, plays a vital role in forming and developing autophagosomes. Therefore, we speculate that the use of 3-MA may reduce cisplatin resistance in hypopharyngeal squamous cell carcinoma (HSCC). Methods: Part I: Cisplatin-resistant FaDu cell line (Human hypopharyngeal squamous cell carcinoma cells) was established and cultured. Cell counting kit-8 was used to detect drug resistance. An inverted microscope was used to observe the morphological changes at different concentrations, then the survival rate was calculated. After MDC staining, the autophagic vacuoles were observed by fluorescence microscopy. The expression of Beclin1 from each group was confirmed by RT-PCR and Western blot method. Part II: 3-MA was applied for cisplatin-resistant cells intervention, Beclin1 was knocked down by plasmid transfection. Cell cycle was detected using flow cytometry assay, apoptosis with necrosis was detected by staining with propidium iodide (PI). CCK-8 was used to observe the cell survival rate in each group. The expression of autophagy-related protein Beclin1, LC3I, LC3II, Atg-5 and P62 in each group was verified by Western blot analysis. Results: Cisplatin-resistant FaDu cell line can be stably constructed by cisplatin intervention. Compared with normal group, autophagy and its related protein Beclin1 expression were enhanced in cisplatin resistant FaDu cells. Autophagy inhibition group showed significant cell cycle changes, mainly manifested by G1 arrest, increased apoptosis rate and significantly decreased survival rate at 24h level. The number of autophagy vacuoles were significantly reduced in the 3-MA group. Furthermore, Western blot showed that expression of Beclin1, lc3-I, lc3-II, atg-5 protein decreased significantly after 3-MA intervention, while the expression of p62 upregulated, which also confirmed autophagy flow was blocked. Conclusion: Our work confirmed that enhanced autophagy is an important cause of cisplatin resistance in FaDu cells. The use of 3-MA can significantly reduce autophagy level and arresting its cell cycle, promote apoptosis and reverse the cisplatin resistance condition, this effect is partly mediated by inhibition of Beclin-1 expression. Our data provide a theoretical basis for the application of 3-MA in overcoming cisplatin resistance in hypopharyngeal cancer.
Keywords: cisplatin-resistance